An introduction to community development - Phillips, Rhonda.; Pittman, Robert H. (Routledge, 2009)
"Beginning with the foundations of community development, this book offers a comprehensive and practical approach to planning for communities. Road-tested in the authors' own teaching, and also through the training they provide for practising planners, it enables students to begin making connections between academic study and practical know-how from both private and public sector contexts. An Introduction to Community Development shows how planners can utilise local economic interests and integrate finance and marketing considerations into their strategy. Most importantly, the book is strongly focused on outcomes, encouraging students to ask: what is best practice when it comes to planning for communities, and how do we accurately measure the results of planning practice? Each chapter provides a range of reading materials for the student, supplemented with text boxes, a chapter outline, keywords, and reference lists, making this the most user-friendly text now available."--BOOK JACKET.